Xylose-assimilating oleaginous yeasts from mangrove forest - Amornrattanapan, Patcharanan; Jhansiri, Napatsawan (Science, Engineering and Health Studies, 2022)
The objectives of this research were to isolate and screen for oleaginous yeasts from leaves and soil samples at Mangrove Forest Conserve and Natural Study Center, Chonburi, Thailand. Investigation of biomass and lipid production of a selected isolated yeast was also conducted to explore the correlation of biomass and lipid production at different time courses. A total of 19 yeast isolates with xylose-assimilating ability were isolated and screened for their potential to accumulate lipid by Sudan black B staining and Nile red fluorescence assay. The results of Sudan black B staining showed that 9 yeast isolates had lipid accumulation in the cytoplasm of yeast cells, and isolate S3-2 was the most promising isolate for lipid accumulation based on the highest level of fluorescence intensity according to Nile red fluorescence assay. Thus, this yeast isolate was selected for the time-course study of biomass production, lipid production and lipid content. Biomass and lipid production achieved from isolate S3-2 were 175.56±1.13 mg/L and 42.59±0.33 mg/L, respectively. The maximum lipid content was determined to be 24.26±0.29% of dry cell weight. These results implied that oleaginous yeasts that could utilize xylose were distributed in mangrove ecosystem, and the strains isolated in this study could be used as a valuable lipid source for future relevant application.